Teachers’ beliefs in ESP teaching for airline staff: Between hopes and realities - Bonifasia Ekta Fima Natalia; Andarwati Andarwati (Research And Innovation In Language Learning (RILL), 2022)
Teachers’ beliefs in ESP have been known as the basis for teachers’ application in their ESP teaching. Teacher beliefs are significant subjects in teacher education that have been designed to help teachers develop their thought and principles. Teachers’ beliefs have a deep impact on their classroom principles. However, facts show that many of what teachers believe fail to be implemented in real teaching activities due to some reasons. This study examines teachers involved in ESP teaching for Airlines Staff at pre-service airlines schools in Indonesian setting. This study aims at (1) knowing teachers’ beliefs in ESP teaching, (2) knowing whether what teacher’s beliefs are implemented in real ESP teaching for airlines staff, (3) knowing teachers’ recommendations for the improvement of the ESP teaching for airlines staff.This study employs qualitative research design. The research data are collected using open ended questionnaire. The collected data are analyzed using data reduction, data display, and conclusion drawing phases. The results of this research indicate that ESP for airlines staff applied in pre-service airlines training schools is still in line with the teachers’ expectations. The recommendations given by the teachers are based on their beliefs in the features or criteria of an ideal or good pre-service training school in ESP teaching for airlines staff.